Relation of Biomarkers of Inflammation and Oxidative Stress with Hypertension Occurrence in Lone Atrial Fibrillation - Marija M. Polovina; Miodrag C. Ostojic; Tatjana S. Potpara (Hindawi Limited, 2015)
We compared plasma levels of biomarkers of inflammation (CRP) and oxidation (oxLDL), determined at study inclusion in lone atrial fibrillation (LAF) patients (48.6±11.5 years; 74.0% men) and sinus rhythm controls (49.7±9.3 years; 72.7% men, P>0.05), and investigated the association of baseline CRP and oxLDL levels with the risk for vascular disease (VD) development (hypertension, cerebrovascular disease, coronary/peripheral artery disease, and pulmonary embolism) during prospective follow-up. Baseline CRP (1.2 [0.7-1.9] mg/L versus 1.1 [0.7-1.6] mg/L) and oxLDL levels (66.3±21.2 U/L versus 57.1±14.6 U/L) were higher in LAF patients (both P<0.05). Following a median of 36 months, incident VD occurred in 14 (28.0%) LAF patients, all of whom developed arterial hypertension, and in 5 (11.4%) controls (hypertension, n=4; coronary artery disease, n=1), P<0.05. LAF patients developed VD more frequently and at a younger age. Both CRP (HR, 2.54; 95% CI, 1.26-5.12; P=0.009) and oxLDL (HR, 2.24; 95% CI, 1.14-4.40; P=0.019) were multivariate predictors of incident hypertension in LAF patients, but not in the controls. Further research should clarify clinical relevance of investigated biomarkers for risk stratification and treatment of LAF patients.